INFLUENCE OF SOME PHOSPHORUS SOURCES AND BIOFERTILIZERS (EM AND PHOSPHOREIN) ON VEGETATIVE GROWTH, FIXED OIL PRODUCTIVITY AND CHEMICAL CONSTITUENTS OF OENOTHERA BIENNIS L. PLANT - Yaser Ghatas; Y. Mohamed (Scientific Journal of Flowers and Ornamental Plants, 2020)
Evening primrose is a beautiful ornamental plant, but at the same time it has medicinal properties that make this plant of great value and importance. In this context, the present research aims to investigate the effect of phosphorus sources and biofertilizers (EM and phosphorein) on growth, flowering, seeds yield, chemical constituents, of Oenothera biennis L. plant. This study was conducted at the Experimental Farm and in the Laboratory of Horticulture Department, Faculty of Agric. at Moshtohor, Benha Univ., Egypt during 2018/2019 and 2019/2020 seasons. The results indicated that, plants which were applied with phosphorus sources, biofertilizers as well as their combination treatments scored highly significant increases in all of studied characteristics of vegetative, flowering, seeds yield, chemical composition, fixed oil percentage, and fatty acids determination of the plant. The maximum values of most parameters mentioned above were gained by the combined treatment of monopotassium phosphate with EM in 1st and 2nd seasons. Additionally, the highest values of flowering parameters and P% were recorded by MAP treatment combined with phosphorein in both seasons. Furthermore, the highest seeds oil percentage (27.22 and 28.37) were recorded by the combined treatment between monopotassium phosphate and phosphorein, in the first and second seasons, respectively. The gained fixed oil composition four components were identified, i.e. palmitic acid, oleic acid, linoleic acid and α-linolenic acid. It can be concluded that the monoamonium phosphate (MAP) or monopotassium phosphate with EM or phosphorein were the best for improving growth, seeds yield, fixed oil productivity, chemical constituents and fixed oil components of Oenothera biennis L. plant.